Presentation of data and control chart analysis (ASTM International, 2018)
"This Manual on the Presentation of Data and Control Chart Analysis was prepared by ASTM's Committee E11 on Quality and Statistics to make available to ASTM Membership, and others, information regarding statistical and quality control methods and to make recommendations for their application in the engineering work of the Society"--